2014
DOI: 10.1371/journal.pone.0108776
|View full text |Cite
|
Sign up to set email alerts
|

21-Benzylidene Digoxin: A Proapoptotic Cardenolide of Cancer Cells That Up-Regulates Na,K-ATPase and Epithelial Tight Junctions

Abstract: Cardiotonic steroids are used to treat heart failure and arrhythmia and have promising anticancer effects. The prototypic cardiotonic steroid ouabain may also be a hormone that modulates epithelial cell adhesion. Cardiotonic steroids consist of a steroid nucleus and a lactone ring, and their biological effects depend on the binding to their receptor, Na,K-ATPase, through which, they inhibit Na+ and K+ ion transport and activate of several intracellular signaling pathways. In this study, we added a styrene grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 110 publications
(112 reference statements)
1
28
0
Order By: Relevance
“…21-BD, considered the template compound, and the only molecule from this group, did not significantly affect the activity of NKA α2 and α3 isoforms ( Figure S1(A) ). Previous studies from our group have demonstrated that 21-BD inhibits the NKA activity derived from a mouse kidney membrane preparation, which only contains the NKA α1 isoform; and has no effect on rat brain NKA, which mainly expresses the NKA α2 and α3 isoforms 18 .…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…21-BD, considered the template compound, and the only molecule from this group, did not significantly affect the activity of NKA α2 and α3 isoforms ( Figure S1(A) ). Previous studies from our group have demonstrated that 21-BD inhibits the NKA activity derived from a mouse kidney membrane preparation, which only contains the NKA α1 isoform; and has no effect on rat brain NKA, which mainly expresses the NKA α2 and α3 isoforms 18 .…”
Section: Resultsmentioning
confidence: 80%
“…We have generated a series of compounds by modifying the lactone ring of the CTS digoxin. One of these synthetic digoxin analogues, 21-benzylidene digoxin (21-BD), presented cytotoxic and antiproliferative effects when used on HeLa cancer cells, via inducing apoptosis in those cells, but inhibiting NKA activity just at high micromolar levels 18 , 19 . Subsequently, starting with the structure of digoxin, we synthesised a series of γ-benzylidene derivatives and showed that they have cytotoxic effects on HeLa and RKO cancer cell lines that are independent from the modulation of NKA activity 20 .…”
Section: Introductionmentioning
confidence: 99%
“…45 A recent study conducted by our research group using the cardiotonic steroid 21-BD showed an augment in Na,K-ATPase levels in canine renal cells (MDCK). 46 Thus, an increased Na,K-ATPase expression in digoxintreated N2a cells ( Figure 6) might be closely associated with the increase of the activity of Na,K-ATPase ( Figure 4). We also evaluated whether N2a cells treated with steroids alone would have any change in enzyme expression.…”
Section: Discussionmentioning
confidence: 85%
“…/K ? -ATPase activity of cardiotonic steroids on cell membrane preparations and intact cells (Oselkin et al 2010;Rocha et al 2014). In intact cells, we have complex modulators of the Na ?…”
Section: Discussionmentioning
confidence: 99%